2017
DOI: 10.5152/npa.2016.13802
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Outcome after Surgery in Patients with Mesial Temporal Lobe Epilepsy

Abstract: Our results showed that patients with left MTLE were not worsened in verbal memory, but despite improved recognition, they have some problems in recalling information and only a minor improvement in attention. Patients with right MTLE improved in their verbal learning capacity, visual memory, and resistance of interference pattern 1 year after surgery. It was thus shown that while epilepsy surgery is associated with some negative cognitive changes, it may also improve some cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…Anterior temporal lobectomy was previously described as improving psychosocial life outcomes including driving, work, independent living, and financial independence (32). However, previous studies had described insignificant differences in neuropsychological outcomes between two procedures (29,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior temporal lobectomy was previously described as improving psychosocial life outcomes including driving, work, independent living, and financial independence (32). However, previous studies had described insignificant differences in neuropsychological outcomes between two procedures (29,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Besides seizure freedom, epilepsy surgery is associated with enhancement of cognitive functions which subsequently had direct and indirect to QoL improvement ( 29 ). We observed that patients who underwent selective amygdalohippocampectomy (SelAH) had a higher overall QoL and energy/fatigue domain compared to those who underwent Anterior temporal lobectomy (ATL) ( p = 0.011 and 0.007, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…De esta manera, la tasa de deterioro de la memoria y el lenguaje es más alta en pacientes que se someten a resecciones del lóbulo temporal izquierdo; por el contrario, los pacientes con resección del lóbulo temporal derecho muestran mejoría o estabilidad en su memoria verbal posoperatoria (16,26,27). Los pacientes sometidos a resecciones del lóbulo temporal derecho presentan deterioro únicamente en su memoria visual, sin que se vean comprometidas otras áreas cognitivas (14,28). Hallazgos empíricos señalan que el principal predictor del nivel de funcionamiento cognitivo posquirúrgico se basa en la integridad de las redes neuronales del paciente.…”
Section: Test Ventaja Desventajaunclassified
“…La evidencia muestra que existe mejora en otras áreas neuropsicológicas, como atención y funciones ejecutivas, sin importar el lado de la intervención (19,28). No se ha encontrado una alteración posquirúrgica significativamente alta en el coeficiente intelectual (CI) de los pacientes sometidos a cirugía del lóbulo temporal, por el contrario, existe mejora o estabilidad en la inteligencia de los pacientes (19,31,32).…”
Section: Test Ventaja Desventajaunclassified